Evaluation or forage legumes of thee genera Centrosema, Galactia and Zornia in acid low fertility soils - Botrel, Milton de Andrade; Pereira, Joaquim Rezende; Xavier, Deise Ferreira (Pesquisa Agropecuaria Brasileira, 2014)
Several accessions of Centrosema, Galactia and Zornia species were evaluated for the potential for forage production, disease and insect resistance, nodulation and mineral content in acid soil of 1ow phosphorus fertility. The experiment was carried out at the Centro Nacional de Pesquisa de Gado de Leite - CNPGL - EMBRAPA; em Coronel Pacheco, MG, Brazil. Only the accessions of G. striata showed a good potential for forage production during the dry season. However, G. striata produces very few seeds, which may endanger its use for forage production. The three genera nodulated abundantly which was reflected in a high concentration of nitrogen in the dry matter, mainly in the accessions of Zornia. Some accession of C. brasilianum and C. virginianum were superior or equal to the standard comercial C. pubescens, in most of the measured parameters.
Keywords: forage production; nutritive value; nodulation